KINERJA USAHA KOPERASI MELALUI PENDEKATAN TINGKAT KESEHATAN KAITANNYA DENGAN PENCIPTAAN VALUE OF FIRM - Dasuki, Rima (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2018)
Savings and Loans Cooperative which is one of the Financial Institutions / Financing which is engaged in the financial services sector de facto has grown and developed rapidly throughout the archipelago and has a central and strategic position in supporting all productive sector productive economic activities. Considering the KSP / USP-Koperasi business activities, one of them is collecting public funds, of course, bringing the consequences that the management of KSP / USP-Koperasi must be handled in a healthy manner by considering the prudent principle. To safeguard and protect the level of public confidence in the KSP / USP-Koperasi from mismanagement or the possibility of possible deviations, KSP / USP-Koperasi or Regency / City Government must monitor and apply an Internal Control System (SPI) which must be implemented by KSP / USP-Koperasi itself on a regular basis. The health of the cooperative will greatly affect the value of the firm's co-operative and the benefits that the member will receive. This study is an early stage for conducting cooperative business performance research through health level approach in relation to the creation of value of firm and share holder equity, financed by Kemenristek Dikti fiscal year 2018.